DESIGN OF AN AUTOMATIC HANDWASHING TOOL USING INFRARED SENSOR BASED ON ARDUINO NANO IN PHYSICS DEPARTMENT OF SRIWIJAYA UNIVERSITY - Annisa, Risa; Saleh, Khairul; Bahtiar, Muhammad Rizki; Rodzikin , Arifu Rahman Bastari (Universitas Mataram, 2024)
The implementation of the New Normal forces people in Indonesia to be able to return to their activities outside the home, alongside the risk of the COVID19 outbreak. One of the health protocols that must be applied is hand washing, so that the use of automatic hand washing devices is very effective in use. The way this automatic hand washing tool works is simply pointing your hand near the sensor, the sensor will detect it. The Automatic Hand Washing Tool is designed using a sensor Infrared, Arduino nano, a module Relay, a water pump and a solenoid faucet. Where is the working principle when thesensor infrared detects an obstacle, it will send an input signal to arduino nano as a microcontroller center which is regulated through a program in the Arduino Ide software, then sends it to themodule relay as answitch on / off, When on it is, themodule relay will activate the solenoid faucet, if it is in thecondition off , the relay will deactivate the solenoid valve, while the pump is used for washing soapy water, where the automatic hand washing tool on water with soapy water is differentiated according to the respective distance that has been set on the arduino nano microcontroller.